Analysis Of The Information Processing Learning Implementation In Indonesian Debate Material In High School - Sutra, Sutra; Nurhadi, Nurhadi; Swatika Sari, Esti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
In 21st century learning, it is important for students to master the intellectual abilities of critical thinking and problem solving. Indonesian subject matter that is in accordance with this mission is debate material. This study aims to describe the analysis of the implementation of information processing learning in Indonesian debate materials in class X SMA Negeri 2 Nunukan. This research was conducted because the learning of information processing in Indonesian debate material trains students in critical thinking and reinforces character education values as demanded by 21st Century learning. This research uses a qualitative descriptive method. The data used in this study are observation notes, documentation, and interviews of class X.MIPA.1 students at SMA Negeri 2 Nunukan in learning Indonesian on debate material. Based on data analysis, it was found that the implementation of the information processing learning model can make students more actively involved in processing or processing information to improve their capabilities in Indonesian debate material. From this learning model, the learning strategy that is in accordance with the character of class X.MIPA.1 students at SMA Negeri 2 Nunukan in implementing information processing learning in Indonesian debate material is an inductive thinking strategy.